Spectrum of histiocytic neoplasms associated with diverse haematological malignancies bearing the same oncogenic mutation. (27th August 2020) - Kemps, Paul G; Hebeda, Konnie M; Pals, Steven T; Verdijk, Robert M; Lam, King H; Bruggink, Annette H; de Lil, Heleen S; Ruiterkamp, Bart; de Heer, Koen; van Laar, Jan AM; Valk, Peter JM; Mutsaers, Pim; et al.
Abstract: Histiocytic disorders are a spectrum of rare diseases characterised by the accumulation of macrophage‐, dendritic cell‐, or monocyte‐differentiated cells in various tissues and organs. The discovery of recurrent genetic alterations in many of these histiocytoses has led to their recognition as clonal neoplastic diseases. Moreover, the identification of the same somatic mutation in histiocytic lesions and peripheral blood and/or bone marrow cells from histiocytosis patients has provided evidence for systemic histiocytic neoplasms to originate from haematopoietic stem/progenitor cells (HSPCs). Here, we investigated associations between histiocytic disorders and additional haematological malignancies bearing the same genetic alteration(s) using the nationwide Dutch Pathology Registry. By searching on pathologist‐assigned diagnostic terms for the various histiocytic disorders, we identified 4602 patients with a putative histopathological diagnosis of a histiocytic disorder between 1971 and 2019. Histiocytosis‐affected tissue samples of 187 patients had been analysed for genetic alterations as part of routine molecular diagnostics, including from nine patients with an additional haematological malignancy. Among these patients, we discovered three cases with different histiocytic neoplasms and additional haematological malignancies bearing identical oncogenic mutations, including one patient with concomitant KRAS p.A59E mutated histiocytic sarcoma and chronic myelomonocytic leukaemia (CMML), one patient with synchronous NRAS p.G12V mutated indeterminate cell histiocytosis and CMML, and one patient with subsequent NRAS p.Q61R mutated Erdheim–Chester disease and acute myeloid leukaemia. These cases support the existence of a common haematopoietic cell‐of‐origin in at least a proportion of patients with a histiocytic neoplasm and additional haematological malignancy. In addition, they suggest that driver mutations in particular genes (e.g. N / KRAS ) may specifically predispose to the development of an additional clonally related haematological malignancy or secondary histiocytic neoplasm. Finally, the putative existence of derailed multipotent HSPCs in these patients emphasises the importance of adequate (bone marrow) staging, molecular analysis and long‐term follow‐up of all histiocytosis patients.